ENVENOMATIONS BY COLUBRIDS: CASE REPORTS - Jackson Lima de Almeida, Breno; Santos Monteiro de Almeida, Milena; Whitney Weekes, Keya; Apolônia da Costa Gadelha, Maria; Pereira de Oliveira Pardal, Pedro (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Introduction: Envenomations by non-venomous snakes in Brazil are poorly accounted for and classified as mild, in which pain, erythema and local edema are reported. Objective: To describe accidents by Philodryas olfersii and Hydrodynastes gigas that occurred in the State of Pará, Brazil. Case report: The patient bitten by Philodryas presented bleeding, pain, local edema and axillary adenopathy. The patient bitten by Hydrodynastes had pain, local growing edema, as well as ecchymosis, fever and headache. No laboratory tests were performed. The treatment was based on pain control after identification of the snakes. Conclusion: The local symptomatology of colubrids is similar to accidents with Bothrops. It is important that health professionals perform a correct diagnosis for proper treatment